Diagnosis and management of intramural ectopic pregnancy. (5th August 2013) - Memtsa, M.; Jamil, A.; Sebire, N.; Jauniaux, E.; Jurkovic, D.
ABSTRACT: Intramural pregnancy is a rare form of ectopic pregnancy, and little is known about its etiology, prevalence and natural history. There is no consensus regarding the ultrasound criteria necessary for the diagnosis of intramural pregnancy, and management strategies vary depending on the severity of clinical presentation, exact location of the pregnancy, viability and gestational age at diagnosis. We present four cases of intramural pregnancy diagnosed in a single institution that illustrate variability in their clinical presentation and difficulty in reaching the correct diagnosis. We also propose a set of ultrasound criteria to facilitate differential diagnosis between intramural and other types of uterine ectopic pregnancy. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.